Effectiveness of Oral Symptom Management in Head and Neck Cancer Patients Receiving Concurrent Chemotherapy and Radiation Therapy (International Journal of Studies in Nursing, 2025)
The purpose of this study is to understand the management of oral symptoms in patients with head and neck cancer receiving concurrent chemotherapy and radiation therapy in the past 10 years. Keywords Settings" oral cancer or head and neck cancer,‖ symptom management or symptom control or relief or improvement symptom management or symptom control or remission or relief or improvement‖, ―CCRT or concurrent chemoradiotherapy‖ and oral health or oral hygiene or oral care, A total of 160 articles were searched between January 2014 and December 31, 2024 through PubMed, EBSCOhost, Embase and Airitilibrary. After removing duplications and publications with inconsistency in the themes, 13 publications were included. The study results revealed the efficacy of oral symptom management for head and neck cancer patients during concurrent chemotherapy and radiation therapy. The results can serve as a reference for medical and nursing personnel in developing strategies to manage oral symptoms among families of head and neck cancer patients undergoing concurrent radiation and chemotherapy. These strategies aim to reduce treatment-related discomfort and improve oral comfort during cancer therapy.